2021
DOI: 10.3390/mi12070832
|View full text |Cite
|
Sign up to set email alerts
|

An In Vivo Microfluidic Study of Bacterial Load Dynamics and Absorption in the C. elegans Intestine

Abstract: Caenorhabditiselegans (C. elegans) has gained importance as a model for studying host-microbiota interactions and bacterial infections related to human pathogens. Assessing the fate of ingested bacteria in the worm’s intestine is therefore of great interest, in particular with respect to normal bacterial digestion or intestinal colonization by pathogens. Here, we report an in vivo study of bacteria in the gut of C. elegans. We take advantage of a polydimethylsiloxane (PDMS) microfluidic device enabling passive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…The single-worm culture method isolates individual C. elegans on small NGM pads, allowing a more direct comparison to the majority of previous studies that use C. elegans to examine host-microbe interactions on solid media, and distinguishing this system from related methods that use microfluidic systems to monitor bacterial infection. 13 The enclosed chamber is humidified with water absorbing beads, allowing for long-term cultivation of animals for repeated sampling of infection data and monitoring of longevity ( Fig. 1c,d ).…”
Section: Resultsmentioning
confidence: 99%
“…The single-worm culture method isolates individual C. elegans on small NGM pads, allowing a more direct comparison to the majority of previous studies that use C. elegans to examine host-microbe interactions on solid media, and distinguishing this system from related methods that use microfluidic systems to monitor bacterial infection. 13 The enclosed chamber is humidified with water absorbing beads, allowing for long-term cultivation of animals for repeated sampling of infection data and monitoring of longevity ( Fig. 1c,d ).…”
Section: Resultsmentioning
confidence: 99%
“…Both of these phenotypes can be tracked in vivo using microuidic solutions. 21,28 Moreover, infection with bacteria can also damage the intestinal cells. For example, it has been reported that S. marcescens is a pathogen of the worm that over time causes vacuolation of the intestinal cells and reduces the volume of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…In the more recent works by Viri et al , 27,28 the dynamics of bacterial transition, load and absorption in the gut of the worms are studied in an automated fashion through fluorescence imaging. The first microfluidic device 27 contained 4 channels, each of which comprised 5 consecutive chambers, separated by filter structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean gut residence time is reportedly < 2 min; approximately 43 ± 10% of the maximum volume of the intestinal lumen is expelled through the anus during each activation of the DMP 22 . The estimated time constant needed for digestion of bacteria is 14 ± 4 s 24 . We previously reported that a C. elegans worm must eat at least three bacterial cells per second to survive for 3 days, which implies the consumption of hundreds of thousands of bacteria daily 39 .…”
Section: Introductionmentioning
confidence: 99%